PERUBAHAN SELULER DAN MOLEKULER PADA NEFROPATI DIABETIK - Sulistyoningrum, Evy (MANDALA of Health, 2014)
Diabetic nehropathy is the most prevalent complication of diabetes mellitus. Hiperglycemia in diabetes mellitus activates several pathways leading to PKC activation. This activation then induce molecular changes involving many growth factors and cytokines. Various growth factors and cytokines further induce extracellular matrix accumulation and mesangial cell expansion leading to glomerular hypertrophy and sclerosis. This changes affects renal function in filtering albumin and further damage can cause abnormal renal function and lead to renal failure